PENAMBAHAN SARI JERUK NIPIS TERHADAP KARAKTERISTIK SIRUP LABU SIAM - M. Adetya Hidayat; Netty Herawati; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to obtain the ratio of chayote extracts and lime extractsin the manufactured of syrup. This research used Complete Randomized Design (CRD) with four treatments and four replication which followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatments in this research included LS0(ratio of chayote extracts and lime extracts 100 : 0), LS1 (ratio chayote extracts and lime extracts 95 : 05), LS2 (ratio chayote extracts and lime extracts 90 : 10), LS3 (chayote extracts and lime extracts 85 : 15). The results of analysis showed that the ratio of chayote extracts and lime extracts significantly effect on acidity (pH), viscosity, total dissolve, sucrose content and organoleptic value (colour, flavour, taste, consistency and overall acceptability). The bestsyrup was LS3 with acidity (pH) 4,45, viscosity 528,33cP, total dissolved 71,03 brix, sucrose content 65,44%. Overall preferred by the panelists with description the colour of rather murky, not falvorful chayote and falvorful lime, sweet taste little  acidic and condensed.   Keywords: Syrup, chayote, lime.